Preliminary data of familial hypercholesterolemia (FH) patients in Romania. (October 2018) - Dumitrescu, Andreea; Mosteoru, Svetlana; Vinereanu, Dragos; Dan, Gheorghe A.; Gaita, Laura; Gaita, Dan
Abstract: Background and aims: Familial hypercholesterolemia (FH) is one of the most frequent monogenic cholesterol disorders. Its prevalence varies in adults between 1/500–1/217 individuals in the heterozygous form. The objective of this study was to uncover the FH prevalence in Romania to perform an adequate prevention for high risk individuals. Methods: We have conducted an epidemiological study between January 2015 and January 2018 by recruiting patients from the CardioPrevent Foundation based on their FH score (taking into account their low density lipoprotein cholesterol (LDLc) levels, clinical characteristics such as premature coronary artery disease (CAD), and their family history of premature cardiovascular disease). We have calculated the probability of FH using the Dutch Lipid Clinic Network (DLCN) criteria and we have included patients with a score over 3 points. Results: We have enrolled 59 patients, out of whom 61% were females. 8.4% of the patients recruited had a first degree relative with premature coronary artery disease and 5% had a relative with LDLc >190 mg/dl (without statin treatment). 10.16% of the patients had coronary artery disease and 15.25% peripheral vascular disease. 91.52% of the patients had a possible FH, while 6.7% had a probable FH and 1.6% a definite FH diagnosis. Based on this data, the prevalence of FH in Romania is: 1:213. Conclusions: To raise the suspicion for FH is easy at the level of the general practitioners, based on the analysis of LDLc levels and premature CAD occurrence. Diagnosis can be further refined using an available online free software. Highlights: We have enrolled 59 patients (0.7%) who had a FH score above 3. The mean LDL-c level upon enrollment was 229.84 mg/dl for the untreated patients. 91.52% of the patients had a possible FH score, while 6.7% a probable FH score and 1.6% had a definite FH score. Based on this data the prevalence of FH in Romania is: 1:213.